A randomized, double-blind, phase III, non-inferiority clinical trial comparing the efficacy and safety of TA4415V (a proposed Trastuzumab biosimilar) and Herceptin (Trastuzumab reference product) in HER2-positive early-stage breast Cancer patients - Reza Safaei Nodehi; Behjat Kalantari; Jahangir Raafat; Nafiseh Ansarinejad; Vahid Moazed; Seyed Mohammad Reza Mortazavizadeh; Mehran Hosseinzadeh; Bayazid Ghaderi; Arash Jenabian; Mojtaba Qadyani; Shirin Haghighat; Abolghasem Allahyari; et al. (BMC, 2022)
Abstract Background This study compared efficacy and safety of TA4415V, a trastuzumab biosimilar, with reference trastuzumab in patients with human epidermal growth factor receptor 2-positive (HER2-positive) early-stage breast cancer treated in the neoadjuvant setting in Iran. Methods Patients were randomly assigned to receive neoadjuvant TA4415V or reference trastuzumab concurrently with docetaxel (TH phase) for 4 cycles after treatment with 4 cycles of doxorubicin and cyclophosphamide (AC phase). Chemotherapy was followed by surgery. The primary endpoint was the comparison of pathologic complete response (pCR) rate in the per-protocol population. Secondary endpoints included comparisons of overall response rate (ORR), breast-conserving surgery (BCS), safety, and immunogenicity. Results Ninety-two participants were analyzed in the per-protocol population (TA4415V, n = 48; reference trastuzumab, n = 44). The pCR rates were 37.50% and 34.09% with TA4415V and reference drug, respectively. The 95% CI of the estimated treatment outcome difference (− 0·03 [95% CI − 0.23 to 0.16]) was within the non-inferiority margin. No statistically significant difference was observed between the groups for other efficacy variables in the ITT population: ORR (89.13% vs. 83.33%; p = 0.72) and BCS (20.37% vs. 12.96%; p = 0.42) in the TA4415V and reference drug group, respectively. At least one grade 3 or 4 adverse events occurred in 27 (50%) patients in the TA4415V group versus 29 (53.70%) in the reference trastuzumab group (p = 0.70). The decrease in left ventricular ejection fraction (LVEF), as an adverse event of special interest (AESI) for trastuzumab, was compared between treatment groups in TH phase. Results demonstrated an LVEF decrease in 7 (12.96%) and 9 (16.67%) patients in TA4415V and reference trastuzumab groups, respectively (p = 0.59). Anti-drug antibodies (ADA) were not detected in any samples of groups. Conclusions Non-inferiority for efficacy was demonstrated between TA4415V and Herceptin based on the ratio of pCR rates in HER2-positive early breast cancer patients. In addition, ORR and BCS, as secondary endpoints, were not significantly different. Safety profile and immunogenicity were also comparable between the two groups.